Low NAD+ Levels Are Associated With a Decline of Spermatogenesis in Transgenic ANDY and Aging Mice - Meyer-Ficca, Mirella L.; Zwerdling, Alexie E.; Swanson, Corey A.; Tucker, Abby G.; Lopez, Sierra A.; Wandersee, Miles K.; Warner, Gina M.; Thompson, Katie L.; Chini, Claudia C.S.; Chen, Haolin; Chini, Eduardo N.; Meyer, Ralph G. (Frontiers in Endocrinology, 2022)
Advanced paternal age has increasingly been recognized as a risk factor for male fertility and progeny health. While underlying causes are not well understood, aging is associated with a continuous decline of blood and tissue NAD+ levels, as well as a decline of testicular functions. The important basic question to what extent ageing-related NAD+ decline is functionally linked to decreased male fertility has been difficult to address due to the pleiotropic effects of aging, and the lack of a suitable animal model in which NAD+ levels can be lowered experimentally in chronologically young adult males. We therefore developed a transgenic mouse model of acquired niacin dependency (ANDY), in which NAD+ levels can be experimentally lowered using a niacin-deficient, chemically defined diet. Using ANDY mice, this report demonstrates for the first time that decreasing body-wide NAD+ levels in young adult mice, including in the testes, to levels that match or exceed the natural NAD+ decline observed in old mice, results in the disruption of spermatogenesis with small testis sizes and reduced sperm counts. ANDY mice are dependent on dietary vitamin B3 (niacin) for NAD+ synthesis, similar to humans. NAD+-deficiency the animals develop on a niacin-free diet is reversed by niacin supplementation. Providing niacin to NAD+-depleted ANDY mice fully rescued spermatogenesis and restored normal testis weight in the animals. The results suggest that NAD+ is important for proper spermatogenesis and that its declining levels during aging are functionally linked to declining spermatogenesis and male fertility. Functions of NAD+ in retinoic acid synthesis, which is an essential testicular signaling pathway regulating spermatogonial proliferation and differentiation, may offer a plausible mechanism for the hypospermatogenesis observed in NAD+-deficient mice.